An Analysis of Cohesiveness in Farming Groups - Agunbiade, J. B.; Ekpere, J. A. (Faculty of Agriculture, University of Ife, 2015)
The concept of group farming has been introduced, developed and accepted in Oyo State as a workable strategy for accelerated technology transfer and food production in the recent past. Evidence of such a policy is shown by the high input delivery and technical advisory assistance that such groups have received from the Ministry of Agriculture and Natural Resources, the Agricultural Credit Corporation and other functionaries of Government in Oyo State. However, the expected advantages of group processes in agricultura1 production, input delivery and technology transfer has been difficult to implement in reality. A major constraint to the effective utilization of farming groups is the relative levels of cohesiveness consistent with sustained survival and operational efficiency essential to the attainment of group goals. In order to better understand this important phenomenon, a study was conducted to investigate cohesiveness within maize production groups in Oyo State. A total of two hundred and two members of ten group farms in two ecological areas of Oyo State were interviewed using a combination of interview schedule and pre-coded questionnaire. The results show that group cohesiveness was affected by access by individuals to group on-lending loan facilities, magnitude of shared profit (or perceived profit), quality of group leadership and individual member objective for group membership. Increasing attrition rates among members due perhaps, to unfulfilled personal expectation was the most single important reason for lack of cohesiveness within the farming groups.